The Quality of the Audiobook for Teaching English to Eleventh-Grade, Second-Semester Visually Impaired Students at SLB N 1 Tabanan - Pujayanthi, Putu; Kusuma, I Putu Indra; Pratiwi, Ni Putu Astiti; Ana, I Ketut Trika Adi (Universitas Pamulang, 2026)
This study aimed to evaluate the quality of an English audiobook developed for eleventh-grade visually impaired students at SLB Negeri 1 Tabanan. The study addressed the need for accessible and pedagogically sound English learning media that align with the auditory learning characteristics of visually impaired students. A mixed-methods approach was employed, combining qualitative and quantitative data. Data were collected through observation, interviews, document study, and expert judgment. The audiobook was evaluated by two experts in English Language Education using a Material Quality Assessment Sheet adapted from Tomlinson’s framework for good language learning materials. Quantitative data were analyzed using descriptive statistics to determine the overall quality of the audiobook, while qualitative data supported the interpretation of the evaluation results. The findings revealed that all evaluated aspects of the audiobook met acceptable quality standards, with most criteria categorized as Good and several aspects achieving an Excellent level. The results indicate that the audiobook is pedagogically appropriate, accessible, and suitable as an English learning medium for visually impaired students. Thus, the study confirms that audiobooks developed through a theory-based and expert-informed approach can effectively support inclusive English language learning. Furthermore, the findings support the integration of audiobooks as an alternative or complementary medium in special education settings, offering practical implications for teachers, material developers, and researchers seeking to improve English learning accessibility and quality for visually impaired students.